Implementation of Blockchain Technology in Learning Management System (LMS) - Rahardja, Untung; Aini, Qurotul; Khairunisa, Alfiah; Sunarya, Po Abas; Millah, Shofiyul (APTISI Transactions on Management (ATM), 2022)
It is well known by the public that the development of science and technology has progressed very rapidly and even continues to increase from year to year, especially in the education system. But in reality, there are still many learning systems that use conventional methods. This method makes the learning process passive and inactive. But now by implementing blockchain into the online learning process and there is no conventional learning process that makes learning activities boring and technology-saturated in the educational learning system at Raharja University, making the learning process more effective and efficient. The objectives of using blockchain technology in education include developing educational curricula, improving the use of educational applications, processing data about education. The research method is carried out by collecting data and using the literature study. So that the presence of blockchain technology makes the education system at the forefront. This application is done so that the learning system can be done with easy access, without being limited by space and time so that it is more efficient. It can even motivate to increase exploration in the learning process which in turn will increase student productivity, of course.